2017
DOI: 10.1080/03014460.2017.1388845
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in BMIz-scores among 45 414 2–4-year olds with severe obesity

Abstract: Background BMI z-scores (BMIz) based on the Centers for Disease Control and Prevention (CDC) growth charts among children do not accurately characterise BMI levels among children with very high BMIs. These limitations may be particularly relevant in longitudinal and intervention studies, as the large changes in the L (normality) and S (dispersion) parameters with age can influence BMIz. Aim To compare longitudinal changes in BMIz with BMI expressed as a percentage of the 95th percentile (%BMIp95) and a modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…1,16,[34][35][36][37][38] Additionally, we found that fat mass varied widely in children of healthy body weights and the application of BMI/BMI95 performed as well, if not better, than weight or BMI. 37 Finally, the utility of the BF% in clinical PK trials requires experimental verification. Obesity will not be associated with altered PK for every drug, yet studies done primarily in adults have identified some physical drug properties, as well as mechanisms of metabolism and elimination, that are more likely associated with altered PK in children and adolescents with obesity.…”
Section: Body Fat Percentagementioning
confidence: 63%
“…1,16,[34][35][36][37][38] Additionally, we found that fat mass varied widely in children of healthy body weights and the application of BMI/BMI95 performed as well, if not better, than weight or BMI. 37 Finally, the utility of the BF% in clinical PK trials requires experimental verification. Obesity will not be associated with altered PK for every drug, yet studies done primarily in adults have identified some physical drug properties, as well as mechanisms of metabolism and elimination, that are more likely associated with altered PK in children and adolescents with obesity.…”
Section: Body Fat Percentagementioning
confidence: 63%
“…In our sample, 26.7% of children have BMI over 95th percentile. Second, in longitudinal and intervention studies the changes in L (normality) and S (dispersion) parameters are particularly large in very high BMI children and cause even more instability in zBMI [29, 30, 37].…”
Section: Discussionmentioning
confidence: 99%
“…Another study used data for adolescents with obesity to demonstrate that change in BMI had greater statistical power than change in BMIz (11). Among a cohort of preschool children with severe obesity who had two measures (mean interval of 11 months), the tracking, as measured by intraclass correlations of the two measures, was better for %BMI p95 and BMImz than for BMIz (12). Longitudinal data from the Bogalusa Heart Study of nearly 7,000 children with two or more measurements found that among the 247 children with severe obesity, BMIz tracked weakly and that repeated measures of %BMI p95 and of BMImz both had correlations of > 0.6 (13).…”
Section: Pediatric Obesitymentioning
confidence: 99%